Decomposition of Educational Objectives in the Context of Hermeneutic Experience of Future Music Teachers - Oleksiuk, Olga; Koval, Anastasiia; Rakhmanova, Oksana (Journal of History Culture and Art Research, 2018)
The modern stage of education and science development witnesses a need in competent teachers capable of showing high adaptability, who are ready to address new pedagogical tasks and embrace active innovations, as well as shift away from stereotypes and conventionality of the educational process. The educational process as such has hermeneutic sense, because in this very process the change of major forms of a subject’s cognitive activity occurs, as we are referring to the formation of a subject who not only understands but also is also capable of interpreting their experience. The phenomenon of hermeneutic experience integrates the world of notions, images, spiritual experiences through which the subjects of the pedagogical process make transformations necessary for the comprehension of the Truth, as it helps to discover the integrity and the moral in the context of understanding the texts of culture. Hermeneutic experience is one of the significant aspects of professional training of future music teachers. That is why decomposition of educational objectives becomes topical, as it can refocus the aim of the educational process from forming knowledge, abilities and skills to forming hermeneutic experience of future music teachers.